Residents Satisfaction SURVEY On The Selected Government's Double Storey Terrace Housing Units At Precinct 9, Federal Territory Of Putrajaya, Malaysia - Precinct With No-Fence Concept. - Talib, Roslan (2009)

(untitled)
With the stages completion of the office buildings at the Government Office Precincts, staff have been relocating themselves from the previous office complex in Kuala Lumpur to Putrajaya and tend to let themselves as fulltime Putrajaya residents.